Cardiovascular Manifestations, Imaging, and Outcomes in Systemic Lupus Erythematosus: An Eight-Year Single Center Experience in the United States. (October 2022) - Ming Wang, Tom Kai; Chan, Nicholas; Khayata, Mohamed; Flanagan, Patrick; Grimm, Richard A; Griffin, Brian P; Husni, M. Elaine; Littlejohn, Emily; Xu, Bo
Systemic lupus erythematosus (SLE) is a challenging autoimmune and multi-system condition. With advances in cardiovascular screening and therapies for SLE patients, we evaluated the cardiovascular characteristics, multi-modality imaging, and outcomes of SLE at our tertiary referral center over an 8 year period. Consecutive patients from our SLE registry from April 2012 to March 2020 were retrospectively analyzed. Data pertaining to cardiovascular manifestations, investigations, management, and outcomes were assessed. We studied 258 SLE patients (mean age 42.2 ± 14.7 years); 233 (90.3%) were female. The main cardiac manifestations at index SLE clinic were pericardial disease in 33.3%, valve disease in 18%, cardiomyopathy in 9.6%, and stroke in 7.4%. During a mean follow-up of 3.0 ± 2.2 years after index SLE clinic, there were 5 (1.9%) deaths, 24 (9.3%) cardiovascular events, and 44 (17.1%) SLE-related hospitalizations. A history of stroke and hypertension were independently associated with cardiovascular events, hazard ratio (HR) (95% confidence intervals (CI)) of 5.38 (1.41–20.6) and 3.31 (1.02–10.7), respectively, while younger age and lower albumin predicted SLE-related hospitalizations. Cardiovascular manifestations are prevalent in SLE, especially for pericardial, valvular, and atherosclerotic diseases. With contemporary SLE and cardiovascular management, subsequent adverse cardiovascular events were infrequent in this study.